Quantifying road-user cost savings and change in land value: a UK case study. Issue 6 (21st December 2020) - Al-Mumaiz, Maha; Evdorides, Harry
Abstract : This paper presents a study on the impacts of an inter-urban road development in the UK through a comprehensive investigation and clarification of the relationship between road-user benefits as a primary impact and changes in land values (CLVs) as a secondary impact. It seeks to offer a methodology aiming at coupling the conventional cost–benefit analysis (CBA) with aspects of economic impact analysis by avoiding double-counting of the results. The CBA model of an existing highway management tool was used to calculate road-user cost savings (RUCSs) of generated traffic, while CLVs were calculated over the same period using a statistical model newly developed for the purpose. A comparison of a 30-year time span was used to test similarities in trends of road-user benefits and CLVs. The main factors affecting the degree of similarity were found to be traffic and its prediction and, in particular, the traffic generated by the new road. It appears that over a 30-year period, a new road project has a positive effect on land values but a negative effect on RUCSs in the first years after construction. The latter increases for about 15 years and then follows a decreasing pattern in the last 10 years or so.